The US-China phase one trade deal: An economic analysis of the managed trade agreement - Michael Funke; Adrian Wende (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2022)
In light of the recent tit-for-tat trade dispute between China and the US, interest in quantifying the effects of the so-called phase one agreement has risen. To this end, the paper quantifies the impact of the asymmetric managed trade agreement using a multi-country open-economy dynamic general quilibrium model. Besides assessing the direct implications for China and the US, trade diversion effects are also analyzed. The model-based analysis finds noticeable positive (negative) impacts of the agreement for the US (China) as well as negative spillover effects for countries not directly affected by the managed trade deal due to trade diversion. The impact of possible future trade agreements is also examined.
URN:NBN:fi:bof-202201201031
Keywords: F13; F41; F42; 330; phase one deal; managed trade; open-economy dynamic general equilibrium model; United States; China